Peramalan produksi dan luas panen padi di Provinsi Lampung Periode Tahun 2025-2030 - Hana Aulia; Seviananda Ekaputri; Ahmad Rido Firmansyah; Dewi Rohma Wati (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
This study aims to forecast the rice production and harvested area in Lampung Province to provide a predictive outlook on the region’s rice sector in the coming years. The data used consist of annual time series observations of rice production and harvested area from 1994 to 2024. The forecasting method employed is the Autoregressive Integrated Moving Average (ARIMA), with analytical procedures including stationarity testing, Box–Cox transformation, differencing, model identification through ACF and PACF, parameter estimation, and model selection based on AIC, AICc, and BIC criteria. The results indicate that the ARIMA (0,2,1) model is the most suitable model for both variables, as it exhibits significant parameter estimates and the lowest information criterion values among the candidate models. Based on this model, forecasts for the 2025–2030 period (periods 32–37) show a gradual upward trend in both rice production and harvested area, despite increasing uncertainty over longer forecast horizons. These findings suggest a positive outlook for the rice sector in Lampung Province and can serve as a reference for policymakers and stakeholders in formulating food security strategies and agricultural productivity improvement plans.